PANDANGAN ISLAM TERHADAP PEMANFAATAN MEDIA SOSIAL - Nur Aksin (Jurnal Informatika Upgris, 2016)
There are many examples based on the modernity of technology however, which affects the life (and especially thoughts and views) community and Muslims in this age is social media. If at some previous period, social media use newspapers, radio, television, wire, and other simple equipment, so today has been converted into a more easily with the technology. The most feared consequence is that social media would be more likely as a tool to launch a variety of ideas that will be largely irrelevant, and destructive to the lives according to the law, religious teachings and norms that berlaku.Oleh therefore, we should know more restrictions -batasan that 'should' in the air-the social media, the community and our people will not fall more deeply to the things that are provocative, ambiguous, confusing, and all the things that lead to moral decay and the mindset of the people.